Progress and Prospect of Training on the Health and Quality of Seeds in Bangladesh (Journal of Environmental Science and Natural Resources, 2013)
Training on seed health was first initiated at the Seed Pathology Laboratory in the Department of Plant Pathology, BAU in 1880s. Farmers Block Supervisors and Subject Matter Specialists of DAE, Scientific Officers from SCA and Seed Wing Officers of BADC received the training. A total of 51 training programmes were conducted during the year 1988-2012 where 1003 trainees have been trained. The durations of the training courses ranged from one day to three months depending on the category of trainees. From 2006 to 2010 SPC organized training of six batches for the Post Graduate Certificate courses based on Seed Technology integrated with Seed Pathology. Through training programmes the knowledge and skills of the trainees were evaluated and found eventually changing their attitudes as regards to the health and quality of crop seeds.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14835 J. Environ. Sci. & Natural Resources, 5(2): 307-313 2012